PSIKOLOGI TOKOH UTAMA DALAM NOVEL TRAUMA KARYA BOY CANDRA - Arti, Winda; Seli, Sesilia; Wartiningsih, Agus (Universitas Tanjungpura, 2023)
This study aims to describe the results of the analysis of the psychology of the main character in the novel Trauma by Boy Candra. The research method used is descriptive in the form of qualitative research. The data source of this research is the novel Trauma by Boy Candra and the data is the psychology of the main character related to the id, ego, and superego in the form of words, phrases, sentences that lead to the object of analysis. Data collection techniques using documentary study techniques. The technique of testing the validity of the data is done by observing persistence, triangulation, and referential coverage. The results showed that the psychology of the main character from the id aspect includes smiling reflexes, imagining or imagining, seeking justification, ignoring prohibitions, leaving without permission, waking reflexes, crying sadly, damaging facilities, obeying invitations, saving oneself, falling asleep, daring to face problems, avoiding reality . The psychology of the main character from the ego aspect includes sublimation, thinking before acting, asking out of curiosity, diversion, giving explanations, unselfishness, repression, and being able to accept reality. The psychology of the main character from the aspect of the superego includes accepting punishment, apologizing, listening to parents' advice, saying goodbye, and being grateful. The materials researcher designed a lesson plan that used the novels Trauma by Boy Candra as a special lesson to achieve KD 3.9 and 4.9 for grade XII SMA.